Natural theology in St. Thomas's early doctrine of truth - Waddell, Michael M. (Sapientia, 2004)
One of Thomas Aquinas's great legacies is the clarity of his teaching about the relationships between theology and philosophy, faith and reason, and grace and nature in general. Of course, that clarity has not prevented the occasional dispute over the philosophical or theological status of any number of particular doctrines. And, in fact, a new controversy has recently begun to form around the status of Thomas's doctrine of truth. The dispute turns on whether or not Thomas's doctrine of truth is fundamentally theological. In his book Medieval Philosophy and the Transcendentals: The Case of Thomas Aquinas, Jan Aertsen contends that Thomas's doctrine of the transcendentals is a philosophical teaching. Inasmuch as Thomas takes truth to be one of the transcendentals, Aertsen must, of course, (re)construct Thomas's doctrine of transcendental truth on philosophical grounds—or, as he describes it, without a "theological foundation'. It is worth noting that Aertsen's use of the term "theology" here includes natural theology; thus, in his effort to claim Thomas's doctrine for philosophy, Aertsen goes so far as to eschew even any natural theological underpinnings. On the other side of the dispute, in their recent book Truth in Aquinas, John Milbank and Catherine Pickstock argue that Thomas's doctrine of truth is "inherently theological"2. It is striking that Pickstock and Milbank also use the term "theology" in such a way as to include not only sacra doctrina, but also tenets that most scholars would recognize as "natural theology".